A facile route for preparing nickel(ii) oxide thin films for high-performance inverted perovskite solar cells. Issue 7 (18th May 2020) - Shen, Guibin; Dong, Hongye; Cai, Qingbin; Wen, Xiaoning; Xu, Xiangning; Mu, Cheng
Abstract : An inverted MAPbI3 perovskite solar cell based on NiO fabricated by a facile low-temperature process realized a PCE of 17.78%. Abstract : Perovskite solar cells (PSCs) have been very popular in the field of photovoltaics. In inverted PSC structures, the hole transport layer deposited before the perovskite photoactive layer plays a crucial role in the power conversion efficiencies (PCEs) and ambient stability of the device. Here, we developed a facile method of preparing NiO hole transport layers with the aid of polymethyl methacrylate (PMMA) for inverted perovskite solar cells. Compared with reported fabrication methods, this route has the advantages of simple, low temperature, and low-cost processing. The corresponding devices exhibited a champion power conversion efficiency (PCE) of 17.78% and good stability. Various characterization experiments, XRD, Raman, AFM, SEM, PL studies etc., were carried out to confirm the superior effect of the NiO film prepared by the new method. We believe that this facile route will be a significant contribution for preparing high performance inverted perovskite solar cells.